Drug Prescription Patterns and Cost Analysis of Diabetes Therapy in India: Audit of an Endocrine Practice - Singla, Rajiv (Indian J Endocrinol Metab, 2019)
AIMS: The aim of this study was to analyze the current trend in the use of antidiabetes as well as other drugs for comorbidities along the duration of diabetes. The study also aimed to analyze the direct drug cost to patients. SETTINGS AND DESIGN: Retrospective cross-sectional study. SUBJECTS AND METHODS: Data captured in clinic electronic medical records of an endocrine practice was analyzed. STATISTICAL ANALYSIS USED: Data was analyzed descriptively using machine learning codes on python platform. RESULTS: Records of 489 people who attended the clinic during the 6-month period were retrieved. Data of 403 people with diabetes were analyzed after exclusion of incomplete data. Use of antidiabetic drug increased from 1.44 (0.78) [mean (standard deviation)] in people with a duration of diabetes <5 years to 3.18 (1.05) in people with 20+ years of diabetes. The mean number of antidiabetic drug usage seems to plateau at 15 years of diabetes. About 46% of people with 20+ years of diabetes required insulin therapy. Prescription patterns involving a combination of different drug classes in patients were also analyzed. The cost of diabetes therapy increases linearly along the duration of diabetes. CONCLUSION: This study provides valuable insights on temporal prescription patterns of antidiabetic drugs from an endocrine practice. Metformin remains the most preferred drug across the entire duration of diabetes. Dipeptidyl peptidase-4 inhibitors seem to be fast catching up with sulfonylureas as a second-line treatment after metformin. After 20 years or more of diabetes duration, 46% people would require insulin for glycemic control.